2010
DOI: 10.1037/a0019545
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and relative importance of choice in the classroom.

Abstract: This investigation examined the effects of providing choices among homework assignments on motivation and subsequent academic performance. Students were randomly assigned within classrooms either to receive a choice of homework options or to be assigned an option for all homework in one instructional unit. Conditions were reversed for a second instructional unit. Results revealed that when students received a choice of homework they reported higher intrinsic motivation to do homework, felt more competent regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
182
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(199 citation statements)
references
References 66 publications
12
182
1
4
Order By: Relevance
“…School students who view their teachers as autonomy supportive are more likely to participate in class learning activities for autonomous reasons (Guay et al, 2001). Students operating in class environments that are autonomy supportive are more likely to experience a sense of choice over their actions, and experience interest and enjoyment in class learning activities (Lepper, Corpus, & Iyengar, 2005;Patall, Cooper, & Wynn, 2010;Reeve & Jang, 2006). They are also more likely to invest effort and persist with those activities in the absence of external prompting or reinforcement.…”
Section: The Trans-contextual Modelmentioning
confidence: 99%
“…School students who view their teachers as autonomy supportive are more likely to participate in class learning activities for autonomous reasons (Guay et al, 2001). Students operating in class environments that are autonomy supportive are more likely to experience a sense of choice over their actions, and experience interest and enjoyment in class learning activities (Lepper, Corpus, & Iyengar, 2005;Patall, Cooper, & Wynn, 2010;Reeve & Jang, 2006). They are also more likely to invest effort and persist with those activities in the absence of external prompting or reinforcement.…”
Section: The Trans-contextual Modelmentioning
confidence: 99%
“…Future research could probe more deeply into the exact nature of this relationship to further explain how the belief in free will and trait self-control wield a concerted influence in predicting positive outcomes. The belief in free will may also interact with external environmental factors, such as the degree of choice and autonomy given for individuals (Patall et al, 2008;Patall et al, 2010). Future studies may examine how different environmental factors interact with the belief in free will to affect outcomes.…”
Section: Limitationsmentioning
confidence: 99%
“…Thus, once faced with a certain outcome, those who believe in free will are likely to assume more responsibility, learn better from their mistakes, and work harder toward changing negative outcomes. The perception of choice, positive attitudes toward choice, and the ability to make choices that are affected by the belief in free will are all essential components for success in academic tasks and in college life (Patall, Cooper, & Robinson, 2008;Patall, Cooper, & Wynn, 2010).…”
Section: Belief In Free Will and Academic Performancementioning
confidence: 99%
“…Patall and her colleagues' research (Patall, Cooper, & Robinson, 2008;Patall, Cooper, & Wynn, 2010) have demonstrated that providing students with choices in making decisions about the tasks they engage in enhances task performance, perceived competence and intrinsic motivation. Ryan and Deci (2000a) also argue that when an individual does not feel in control of her/his actions and outcomes, intrinsic motivation is diminished.…”
Section: Exercising Choice In Out-of-class Learningmentioning
confidence: 99%